Study of Efficiency of Islamic Commercial Banks in Indonesia through the Role of Capital and Liquidity: Two-Stage Data Envelopment Analysis - Fitri Irianti; Erie Febrian; Yudi Ahmad Faisal (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
In measuring efficiency in a company which is also often used in the banking industry, namely the DEA (Data Envelopment Analysis) method which compares input and output variables and is one of the optimization methods of mathematical programs. This study will examine the efficiency level of Islamic banking in Indonesia during the 2016-2020 period and see the role of capital and liquidity or their influence on the efficiency level of Islamic banking. The method used is a quantitative method using a non-parametric approach (DEA) and a parametric approach using the Tobit Regression method to see the effect of capital and liquidity. The results show that Islamic Commercial Banks (BUS) in Indonesia have not operated efficiently based on the average efficiency score obtained by the DEA method during the period 2016 to 2020, which is 0,911. Furthermore, the results of the study show that capital and liquidity can build the efficiency level of Islamic Commercial Banks in Indonesia.